2011
DOI: 10.1074/jbc.m111.255869
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase 1 (PARP-1) Binds to 8-Oxoguanine-DNA Glycosylase (OGG1)

Abstract: Background: Oxidative stress-induced DNA damage is repaired by proteins in the base excision pathway. Results: We identified a novel interaction between two DNA repair proteins, OGG1 and PARP-1. Conclusion: OGG1-PARP-1 binding has both a functional and biological consequence. Significance: These results provide insight into the factors that regulate DNA repair under normal and oxidative stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 56 publications
4
100
1
1
Order By: Relevance
“…Additionally, OGG1 activity in other sequence contexts was not altered significantly. It is noteworthy that several other proteins including APE1, x-ray repair cross-complementing protein 1, and poly(ADP-ribose) polymerase 1 influence the removal of 8-oxoG by OGG1 (63)(64)(65). Further studies that examine the influence of other BER proteins/co-factors on the coding potential (polymerase-dependent) and repair of 8-oxoG will provide insights into cooperative protein interactions that modulate the mutagenic potential of an important oxidative DNA lesion in a biologically important sequence context.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OGG1 activity in other sequence contexts was not altered significantly. It is noteworthy that several other proteins including APE1, x-ray repair cross-complementing protein 1, and poly(ADP-ribose) polymerase 1 influence the removal of 8-oxoG by OGG1 (63)(64)(65). Further studies that examine the influence of other BER proteins/co-factors on the coding potential (polymerase-dependent) and repair of 8-oxoG will provide insights into cooperative protein interactions that modulate the mutagenic potential of an important oxidative DNA lesion in a biologically important sequence context.…”
Section: Discussionmentioning
confidence: 99%
“…Histidinetagged homeodomain protein B3 (HOXB3) was obtained from Addgene (72), and GST-tagged OGG1 was a generous gift from Drs. Nicole Noren Hooten and Michele Evans (35). All proteins were expressed in the BL21 strain of E. coli and were induced with isopropyl ␤-D-thiogalactopyranoside.…”
Section: Methodsmentioning
confidence: 99%
“…Both OGG1 and NEIL1 were shown to bind to PARP-1 and stimulate its poly-(ADP-ribosyl)ation activity, thereby promoting the recruitment of downstream BER effectors such as XRCC1. In turn, PARP-1 inhibits the enzymatic activity of these DNA glycosylases (34,35). Globally, the above cited studies indicate that several proteins can participate in BER complex formation and modulate the enzymatic activities of distinct BER enzymes.…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…PARP1 ac vity and PARP1 content generally declines with age, but it was reported to be higher in cells from centenarians than in controls [915]. More recently, it has been reported that OGG1 and NEIL1, two of the mammalian base excision repair glycosylases, bind to PARP1 and s mulate its ac vity [916,917]. PARP1 has been iden fied as a therapeu c target in cancer, with its inhibi on intended to decrease the capacity for DNA repair in cancer cells damaged by radio-and chemotherapy [reviewed in 918].…”
Section: Brca1 and Brca2mentioning
confidence: 99%